Nadzoriyatu Khalqu al-Insân fî al-Kitâb al-Muqoddas: Naqdu ‘alâ Nadzariyati al-Tathowwur lî Charles Darwin (Journal of Comparative Study of Religions, 2024)
This article explores the fundamental differences between these theological and scientific views through analysis of the text of the Bible and Darwin's theory of evolution which aims to explain the definition of human creation and the theory of evolution and analyze the theory using verses in the Bible. To complete this writing, the researcher used the descriptive-critical analysis method to examine and criticize the theory using a naturalist worldview approach to the ideas presented by Darwin. The result is that Charles Darwin's theory of evolution becomes a new paradigm regarding human origins which denies divinity in its creation. Darwin's theory of evolution is a scientific concept which states that living species experience development through the process of natural selection. In the Book of Genesis it explains that humans were created by God, Adam was formed from the dust of the ground and breathed the breath of life into his nose and created Eve from Adam's rib, this shows that humans were created directly by God and are considered special among other creations.